Minor dysmorphic features in a patient with papillorenal syndrome – A Case Report - Ferit Kulali; Ahmet Yagmur Bas; Fatma Iyigun Guzel; Husniye Yucel; Caner Kara; Cigdem Uner; Nihal Demirel (Journal of the Pakistan Medical Association, 2020)
Published in March 2021